THE EFFECTIVENESS OF CONTEXTUAL TEACHING AND LEARNING TO TEACH READING COMPREHENSION VIEWED FROM STUDENTS’ INTELLIGENCE - Kitri Katon Peni (Center of Language and Cultural Studies [CLCS], 2018)
The research examines: (1) the effectiveness of Contextual teaching and learning (CTL) compared to grammar translation method in teaching reading, (2) effect of intelligence quotient to reading comprehension, and (3) interaction between teaching methods and the intelligence in teaching reading. The research was carried out at SMPN 14 Surakarta, using the experimental design assigning 72 students as sample. Data were collected using the documentary and test technique. To analyze the data, Multifactor Analysis of Variance (ANOVA) test of 2x2 and Tukey test were used. The results show that: (1) CTL was more effective than grammar translation method in teaching reading, (2) the students having high intelligence quotient had better reading comprehension than those having low intelligence, and (3) interactions occur between teaching methods and intelligence in teaching reading.